IMPLIKATUR DALAM PERCAKAPAN SINETRON PARA PENCARI TUHAN - Dyah Rohma Wati (Jurnal Penelitian Humaniora, 2017)
The aim of this research is to know conversational implicature in Para PencariTuhan (PPT) TV-series (volume I), especially to know and describe the kinds ofmaxim which float in PPT TV-series (volume I) and to describe the background offloating maxim in conversational implicature at PPT TV-series(volume I). This isqualitative research. The data of this research are conversational implicature ofsome utterances in PPT TV-series (volume I). The source of data is Para PencariTuhan TV-series (volume I, episode I) produced by PT Demi Gisela Citra Sinema.The researcher obtain the data through documentation technique. This techniquestarts by listening whole implicature in PPT TV-series (volume I), taking note wholerelated data, classifying and taking note the data in data card. This research uses flowmodel analysis to analyze the data, which include collecting data, data reduction,data presentation, and conclusion or verification. The data analysis show that thereare floating in some coperative-principle of maxims, they are maxim quality (twoutterances), maxim manner (two utterances), maxim relevance (one utterance).The floating maxim in PPT TV-series are influenced by some factors, they are thesimilarity of presupposition, the speaker refers to certain reference, and the use oflocal interpretation.